Nuts & seeds in health and disease prevention - Preedy, Victor R.; Watson, Ronald R.; Patel, Vinood B. (Academic Press, 2011)
The use of nuts and seeds to improve human nutritional status has proven successful for a variety of conditions including in the treatment of high cholesterol, reduced risk of Type-2 Diabetes, and weight control. This complete guide to the health benefits of nuts and seeds is the only single-source scientific reference to explore the specific factors that contribute to these potential health benefits, as well as discussing how to maximize those potential benefits.